2022
DOI: 10.1111/os.13292
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Treatment Strategy of Isolated Calf Deep Venous Thrombosis after Fractures: A Review of Recent Literature

Abstract: Isolated calf deep venous thrombosis (ICDVT) includes thrombosis located at the far end of the popliteal vein, such as the anterior tibial vein, posterior tibial vein, fibular vein, and intramuscular vein of the soleus and gastrocnemius. This type of thrombosis has the highest incidence, accounting for approximately half of all deep vein thrombosis (DVT) cases; however, there is no consistent recommendation for ICDVT treatment across countries, and there is also no optimal management strategy. In recent years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…22 Previous studies have shown that untreated ICDVT have a tendency for proximal proliferation. 12,13 At 1 month postdischarge, the incidence of proximal propagation and localized calf propagation was 24.56% (n=14) in the DOACs poor compliance group, much higher than in the fair compliance group (7.04%, n=19) and full compliance group (2.4%, n=9), with p<0.001.This highlights the importance of patient compliance to medication regimen in preventing the progression of ICDVT.…”
Section: Discussionmentioning
confidence: 85%
See 3 more Smart Citations
“…22 Previous studies have shown that untreated ICDVT have a tendency for proximal proliferation. 12,13 At 1 month postdischarge, the incidence of proximal propagation and localized calf propagation was 24.56% (n=14) in the DOACs poor compliance group, much higher than in the fair compliance group (7.04%, n=19) and full compliance group (2.4%, n=9), with p<0.001.This highlights the importance of patient compliance to medication regimen in preventing the progression of ICDVT.…”
Section: Discussionmentioning
confidence: 85%
“…Currently, the consistent theory holds that ICDVT is more commonly associated with transient risk factors and less often with permanent, irrevocable risk factors; furthermore, the risk of proximal propagation and recurrence is significantly lower than that of proximal DVT. 11,12 There is insufficient medical-based evidence to support the need for anticoagulation after discharge, particularly in the population of elderly patients with hip fractures. Although some suggestions or guidelines based on a weak level of evidence recommend surveillance compression ultrasound within two weeks of discharge to detect proximal propagation, few patients and clinicians choose to do so in practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…MCVT often goes unnoticed due to mild and non-acute symptoms. However, once a thrombus detaches and enters the lungs through blood circulation, it can cause pulmonary embolism [20]. Therefore, it is crucial in clinical practice to disseminate knowledge about MCVT-related detection and raise awareness among patients and healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%